Identification of arbuscular mycorrhizal fungi in melina (Gmelina arborea Roxb) plantations in the Ecuadorian humid tropics - Meza B., Fabricio (2017)
This study aimed to isolate and identify arbuscular mycorrhizal fungi in melina (Gmelina arborea Roxb) plantations. Two melina plantations of 1 and 3 years old located in the central zone of the humid Ecuadorian tropics, province of Los Ríos, Valencia were sampled. Soil and root samples were collected in the dry season between June and December 2015. The results showed the presence of the arbuscular mycorrhizal fungi genera Glomus and Gigaspora. The genus with the greatest representativeness in quantity of spores per gram of soil was Glomus. The highest percentage of mycorrhizal colonization occurred in the roots of 1-year-old trees.